PHOX2B Immunostaining: A Simple and Helpful Tool for the Recognition of Ganglionic Cells and Diagnosis of Hirschsprung Disease. (October 2020) - Drabent, Philippe; Bonnard, Arnaud; Guimiot, Fabien; Peuchmaur, Michel; Berrebi, Dominique
Abstract : Hirschsprung disease (HD) is a congenital disorder of the enteric nervous system that occurs in ∼1 in 5000 live births. It is characterized by the absence of ganglionic cells (GCs) in the distal intestine. The diagnosis relies on the thorough analysis of a rectal suction biopsy (RSB), which must show a complete absence of GCs after careful examination of at least 100 serial sections. Such a negative characteristic explains the difficulty of this diagnosis. Moreover, GCs may be immature in very young or preterm born children, making them hard to recognize. Therefore, ancillary techniques have been developed as diagnostic help, such as acetylcholinesterase histochemistry and calretinin immunostaining. These techniques reveal only indirect clues, focusing mainly on the changes in nerve fibers, but not on GCs themselves. As PHOX2B has been shown to be a very specific transcription factor in GCs and in progenitor enteric nerve cells, we have assessed (i) PHOX2B immunostaining in immature enteric ganglia and (ii) the use of PHOX2B immunostaining for the recognition of GCs on RSBs for suspicion of HD. We have observed PHOX2B expression in all GCs, both mature and immature, and its complete absence in Hirschsprung cases. We suggest that the use of PHOX2B immunostaining is of great help (i) in the recognition of GCs on RSBs regardless of their differentiation and therefore (ii) in the diagnosis of HD.